Intramuscular lipoma in the left thigh of a woman - Alejandro Martínez Álvarez; Mileidys León Piñeiro; Pedro Armando Candeau Tamayo (Centro Provincial de Información de Ciencias Médicas, 2021)
The case report of a 32 years patient with history of paranoid schizophrenia is described. She was assisted in the Orthopedics and Traumatology Service of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba, due to an increase of volume in the internal face of the left thigh that difficulted her from walking.  A tumor of approximately 20 cm was observed with the physical exam, that was not painful to the palpation, but soft and doughy, with imprecise limits and adhered to deep planes. According to the imaging studies it was an adipose tissue, reason why there was no correlation with the elements obtained with the physical exam. Taking into account the above-mentioned the case was discussed with the imaging specialists and the decision was removing the tumor. A sample for biopsy was taken whose result informed the presence of a lipoma. The woman had a favorable clinical course and she returned to her usual activities 2 months later.